Exploring Community Residents' Motivations for Interacting With American Field School Undergraduates in South Africa. (June 2019) - Wainwright, Megan; Sicwebu, Namhla; Colvin, Christopher J.; Gong, Estelle; Henderson, Rachel; Swartz, Alison
Background: Learning by experience in field schools (FSs) depends implicitly on the willingness of local residents to engage with students. Although critical perspectives have highlighted the potential harms of study abroad on local people, their views are less frequently investigated.Purpose: The purpose of the study is to explore the perspectives and motivations of local residents who agreed to be interviewed by American undergraduates undertaking a 5-week FS in community health research methods in Cape Town, South Africa.Methodology/Approach: Semi-structured interviews were conducted with 23 residents to explore their perspectives on why they, and others, were willing to be interviewed by students. These were thematically analyzed.Findings/Conclusions: Emphasis was given to the status implicit in being "a student" and "a visitor" and the respect, hospitality, and support this status engendered. To be a student was to be a child and not in a position to help. However, expectations were that help would come later. Residents valued the conversations they had which were seen as opportunities for enjoyment, exchange, and bridging social divides.Implications: In experiential learning programs such as these, local residents are a key community learning resource. Certain design features appear to help optimize the engagement and relationship-building valued by students and residents alike.